Narrative paths through Mamre and Sodom the oak and the gate - Suriano, Ambra (T&T Clark, 2025)
"Ambra Suriano analyses the narrator's techniques, exploring the influence of the readers' understanding and playing with their interpretative freedom in recounting particular episodes in the Book of Genesis. She argues that a synchronic analysis of the text uncovers a series of binary oppositions that characterise the narrative world of Mamre and Sodom. Beginning with a summary of the context of Genesis 18-19, Suriano traces the boundaries and narrative coherence of the text, considering each episode as part of a single story and divided into five scenes, which can be further split into narrative units. Within each scene and narrative unit, Suriano considers the dynamics between the narrator and the reader, amongst the characters, between the narrator and the characters and between the reader and the characters, highlighting how they interact with each other and with the narrative world they are programmed for. She proposes that knowledge is the main topic of the narrative, to which all the characters concur; knowledge of the divine and human world, leading to awareness and the critical ability to distinguish between good and evil, and to choose which to follow."
Bevorzugte Informationsquelle: Landingpage des E-Books und/oder Katalogisat der Druckausgabe, da weder Titelseite noch Impressum vorhanden (Bloomsbury Collections)
Keywords: Bible. / Genesis, XVIII-XIX / Criticism, interpretation, etc.; Narration in the Bible.; Biblical studies & exegesis